Facile Synthesis of Crumpled Nitrogen‐Doped MXene Nanosheets as a New Sulfur Host for Lithium–Sulfur Batteries. Issue 13 (11th January 2018) - Bao, Weizhai; Liu, Lin; Wang, Chengyin; Choi, Sinho; Wang, Dan; Wang, Guoxiu
Abstract: Crumpled nitrogen‐doped MXene nanosheets with strong physical and chemical coadsorption of polysulfides are synthesized by a novel one‐step approach and then utilized as a new sulfur host for lithium–sulfur batteries. The nitrogen‐doping strategy enables introduction of heteroatoms into MXene nanosheets and simultaneously induces a well‐defined porous structure, high surface area, and large pore volume. The as‐prepared nitrogen‐doped MXene nanosheets have a strong capability of physical and chemical dual‐adsorption for polysulfides and achieve a high areal sulfur loading of 5.1 mg cm –2 . Lithium–sulfur batteries, based on crumpled nitrogen‐doped MXene nanosheets/sulfur composites, demonstrate outstanding electrochemical performances, including a high reversible capacity (1144 mA h g –1 at 0.2C rate) and an extended cycling stability (610 mA h g –1 at 2C after 1000 cycles). Abstract : A novel strategy is applied to dope nitrogen into MXene frameworks. The resultant nitrogen‐doped MXene nanosheets have a well‐defined crumpled structure, a high surface area, and large pore volume. The nitrogen‐doped crumpled MXene nanosheets demonstrate strong physical and chemical coadsorption of polysulfides. When used as cathode hosts, lithium–sulfur batteries exhibit outstanding electrochemical performance.